Undocumented Domestic Workers and Coronavirus Disease 2019: A Qualitative Study on the Impact of Preventive Measures - van den Muijsenbergh, Maria; Torensma, Marieke; Skowronek, Nathalia; de Lange, Tesseltje; Stronks, Karien (Frontiers in Communication, 2022)
This paper describes qualitative study explores the impact of COVID-19 preventive measures on Uundocumented DmMigrant domestic workers in the Netherlands. Undocumented migrants (UDMUDMs) are likely to experience inequalities due tohigh impact of the COVID-19 pandemic. They rely on the informal market for work and housing, and are usually not entitled to healthcare insurance. However, they are not represented in COVID-19 registrations or surveys. In order to advise policymakers and healthcare professionals how to tailor preventive activities in handling of a pandemic, including vaccination strategy, to the needs of this group insight in their experiences is needed. This qualitative study explores the impact of COVID-19 preventive measures on UDM domestic workers in the Netherlands. MethodsIn our qualitative study Ttwo focus group discussions were held with 14 UDMUDMs, recruited through snowball technique. Discussions addressed knowledge, uptake and impact of the COVID-19 measures in relation to working and living circumstances, health and access to healthcare. Transcripts were analyzed thematically. Results The UDMUDMs perceived COVID-19 as a threat., and the preventive measures as efficacious. Their precarious position affected their perceived vulnerability, which motivated them to seek information on and to comply to preventive measures and testing. However, structural barriers decreased their self-efficacy and opportunity to comply. COVID-19 measures impacted UDMUDM’s’ lives on essential domains, resulting in job, food and housing insecurity and increased barriers in access to healthcare. Discussion and conclusion UDMUDMS precarious position motivates them to seek information on and comply to preventive measures and testing. Structural barriers decrease their self-efficacy and opportunity to comply. An intersectoral approach, addressing health communication, access to healthcare and social support as well as legal rights for safe employment is needed to alleviate the impact of the measures on UDMUDMs.